Stakeholder analysis : drawing methodological lessons from review of relevant literature - Henwood, Ruth (Department of Public Health and Family Medicine, 2017)
Stakeholder analysis (SHA) is an important tool in policy analysis, used to understand the actors who are affected by or have an effect on a particular policy. Its implementation spans a variety of sectors from government to corporate, and conservation to health. The widespread application of SHA naturally causes some confusion with regards to terminology and methodology, but also serves as an opportunity for cross-sectoral and cross-discipline learning. This mini-dissertation discusses methods used to conduct stakeholder analyses (SHAs). It presents, first, the results of a broad scoping review investigating SHA methods described in 28 articles outside the health sector spanning low, middle and high income geographical regions. This scoping review, together with the seminal Varvasovszky and Brugha (2000) health policy SHA guide is, second, used to inform a systematic review – that entails a more critical assessment of the application of SHA across 21 articles addressing the use of SHAs within health policy analysis work undertaken within low to middle income country (LMIC) settings. A variety of methodological approaches to SHAs are used outside of the health sector, including creative ways to generate information in collaboration with SHs, as well as to present SHA findings. Future health policy analysts and researchers would do well to look outside the health sector for more creative and participative data collection and presentation approaches. Notwithstanding the widespread citing of Varvasovsky and Brugha (2000) across health policy SHAs, many of the articles were found wanting in their reflection on key issues presented by Varvasovsky and Brugha (2000). Health policy SH analysts and researchers should consider the use of a two- step SH identification strategy in order to include a greater variety of SHs; offer reflection on their own role within the process of focus and the potential impact of this on the analysis; as well as expand on how context is accounted for in the SHA process, rather than just describing it.